Estimation of erosivity index using daily rainfall for Dehradun, Uttarakhand - KUMAR, PRAVENDRA; TIWARI, SUSHANT; CHANU, SANJARAMBAM NIRUPAMA; LUTHRA, KAUSHIK; RANI, POONAM (Journal of Soil and Water Conservation, 2020)
The present study was undertaken to develop the rainfall erosivity models for Dehradun district, Uttarakhand, India for estimating the erosivity index values and for establishing the most effective relationship between erosivity and daily rainfall values for the study area. For this, two models namely linear and exponential relationship between erosivity and daily rainfall values were developed and results were compared with the model proposed by Central Soil and Water Conservation Research and Training Institute, Dehradun for their suitability in the region. Model performance was evaluated using two statistical indices such as absolute prediction error and coefficient of efficiency. Absolute prediction error was found to be 13.09 % and 19.58 % for linear and exponential relationship respectively whereas coefficient of efficiency was found to be 99.24 % and 98.54 % for linear and exponential relationship respectively. APE of 55.10 % and CE of 45.37 % were found for the model proposed by Central Soil and Water Conservation Research and Training Institute, Dehradun. It was observed that both the developed models are valid for estimating erosivity index values for Dehradun region. However, based on evaluation criteria, the linear model was found to be better than exponential model and it was also observed that the model developed by Central Soil and Water Conservation Research and Training Institute is not applicable for Dehradun region.